Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4293/jsls.2014.00256
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Changes to Decrease Complications in Laparoscopic Gastric Bypass

Abstract: Background and Objectives:Laparoscopic Roux-en-Y gastric bypass (LRYGB) is a complex procedure performed in a patient population with significant medical comorbidities. Evaluation and modification of surgical techniques can minimize the complications associated with the lengthy learning curve for this procedure. The purpose of this study was to evaluate a single surgeon's decade-long experience with LRYGB, to determine whether complications decreased with experience and surgical modifications improved perioper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Another study of robotassisted RYGB found 100 cases on the learning curve to be a discriminator in terms of operative time but without any differences in outcomes or complications (371). This 100-case mark was also reported in a study by Beitner et al (372) for RYGB, in which late complication and re-operation rates were eventually improved with modification in surgical technique. In a Chinese study of patients undergoing RYGB, the learning curve was more associated with operating time and morbidity than mortality or amount of eventual weight loss (373).…”
Section: R5 (2019*)mentioning
confidence: 70%
“…Another study of robotassisted RYGB found 100 cases on the learning curve to be a discriminator in terms of operative time but without any differences in outcomes or complications (371). This 100-case mark was also reported in a study by Beitner et al (372) for RYGB, in which late complication and re-operation rates were eventually improved with modification in surgical technique. In a Chinese study of patients undergoing RYGB, the learning curve was more associated with operating time and morbidity than mortality or amount of eventual weight loss (373).…”
Section: R5 (2019*)mentioning
confidence: 70%
“…This 100‐case mark was also reported in a study by Beitner et al for RYGB, in which late complication and re‐operation rates were eventually improved with modification in surgical technique. In a Chinese study of patients undergoing RYGB, the learning curve was more associated with operating time and morbidity than mortality or amount of eventual weight loss . However, Rausa et al found that the relative superiority of LRYGB over open RYGB may be due to extended learning curves in the former.…”
Section: Executive Summarymentioning
confidence: 99%
“…Laparoscopic RYGB is a complex procedure that requires advanced skills and understandings of key surgical steps [28]. In our study, fellow participation during laparoscopic RYGB was associated with an increased risk of developing complications when compared to non-trainees.…”
Section: Discussionmentioning
confidence: 66%